Pengaruh Kualitas Produk, Harga, Citra Merek dan Pelayanan Terhadap Loyalitas Pelanggan Usaha Toko Roti Bunda Habib - Dwi Rumaisah Hasibuan; Junita Lubis; Nova Jayanti (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of product quality, price, brand image and service on customer loyalty. The sample in this study was 100 respondents, namely customers of Bunda Habib bakery. This study uses validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test, and coefficient of determination using SPSS 24. The results of the study indicate that product quality partially has a positive and significant effect on customer loyalty at Bunda Habib Bakery, Price partially has a positive and significant effect on customer loyalty at Bunda Habib Bakery, Brand image partially has a positive and significant effect on customer loyalty at Bunda Habib Bakery, Service partially has a positive and significant effect on customer loyalty at Bunda Habib Bakery, and Product quality, price, brand image and service simultaneously have a positive and significant effect on customer loyalty at Bunda Habib Bakery